Pengaruh Layanan Aplikasi Dana Terhadap Kepuasan Mahasiswa Banten dalam Transasi Online Sebagai Alat Pembayaran Elektronik - Akbar Pratama Aditya; Nova Aris safitri; Pinkan Dwi Ananda; Wahyu Hidayat; Hadi Perwisto; Fitri (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
With the rapid development of technology and the Internet, more and more people are using electronic payments as a convenient solution for online transactions. The aim of this research is to show and analyze how service quality influences user satisfaction with the DANA electronic payment application. DANA is a platform that supports non-cash payments and mobile payments. This research uses quantitative methods by collecting data through questionnaires distributed to 30 Banten students using DANA. Data analysis was carried out using multiple regression as well as the t test, F test, and coefficient of determination test. The research results show that reliability, guarantee, and responsiveness can have a significant impact on user satisfaction. Overall, reliability, security, and responsiveness also have a significant impact on user satisfaction.